Estratégias experimentais de ensino visando contribuir com o ensino de Física de modo significativo: atividades de eletricidade, magnetismo e eletromagnetismo - Kohori, Rodolfo Kasuyoshi [UNESP] (2015)
The study of Electricity, in the discipline of Physics, has a very extensive content with abstract concepts difficult to understand. As a result, the lack of interest by the study, it becomes a constant among many students. This situation can be partly reversed, adopting experimental activities in the classroom, in order to expose the applicability of the content in practical situations. It proposes a didactic-pedagogic material that exploits the contents of Electricity interactively, in order to stimulate students to understand, to question and to seek more knowledge. For the elaboration of this material was used the following theoretical frameworks: Experimentation in Physics teaching; Lev Semenovitch Vygotsky's theory; David Paul Ausubel and Meaningful Learning; Laurence Stenhouse and the Curriculum of the State of São Paulo. The proposed experiments used low cost and scrap materials. They were applied in the didactical sequence of physics at the 3rd high school grade in a public school and as an introduction to chemistry content. The experiments have facilitated the process of Teaching- Learning, because awakened interest among students, with participation of everyone in the experimental activities. The most problem encountered was the time required for preparation and execution of some experiments and lack of professional technical in the laboratory. The proposed material can be used by teachers of physics and applied in the classroom